The Influence Of Social Media Influencers On The Buying Interest Of The Young Generation With Consumer Attitude As A Mediation Variable - Yuliana, Ade; Novandari, Weni; Setyawati, Sri Murni (Jurnal Fokus Manajemen, 2025)
This research aims to examine the effectiveness of social media influencer advertising on Generation Y and Z, with a focus on source credibility and attractiveness in relation to purchase intention. The study proposes that consumer attitude mediates the relationship between social media influencer characteristics (both exogenous and endogenous) and purchase intention. Structural Equation Modelling (SEM) was employed to test the empirical models, with SMARTPLS and SPSS utilized for the analysis. A total of 193 respondents were sampled. The findings support all the hypotheses except for the direct relationship between source attractiveness and consumer attitudes. Additionally, the study demonstrates that generational differences act as moderating variables in the relationship between consumer attitude and purchase intention.